Critical-layer instability of shallow-water magnetohydrodynamic shear flows. (25th July 2022) - Wang, Chen; Gilbert, Andrew; Mason, Joanne
Abstract: Abstract : In this paper, the instability of shallow-water shear flow with a sheared parallel magnetic field is studied. Waves propagating in such magnetic shear flows encounter critical levels where the phase velocity relative to the basic flow, c-U(y), matches the Alfvén wave velocities ± B(y)/μ ρ , based on the local magnetic field B(y), the magnetic permeability μ, and the mass density of the fluid ρ . It is shown that when the two critical levels are close to each other, the critical layer can generate an instability. The instability problem is solved, combining asymptotic solutions at large wavenumbers and numerical solutions, and the mechanism of instability explained using the conservation of momentum. For the shallow-water magnetohydrodynamic system, the paper gives the general form of the local differential equation governing such coalescing critical layers for any generic field and flow profiles, and determines precisely how the magnetic field modifies the purely hydrodynamic stability criterion based on the potential vorticity gradient in the critical layer. The curvature of the magnetic field profile, or equivalently the electric current gradient J' = - B''/μ in the critical layer, is found to play a complementary role in the instability.